SPECIFIC CHARACTERISTICS OF KHAN CHARAMS IN ARCHITECTURE (Conferencea, 2022)
This article covers the palaces and harems of the Khans, the meaning of the word harem and the opinion of tourists, the Taskhovli architectural monument, the complex and harem of Sitorai Mohi Khosa. About Abdullah Khan's Haramsaroy, which was originally formed by Abdullah Khan in the Chor Bakr complex, but which has disappeared today, opinions are given on the characteristics of the khan's harems.